Differentiated Learning and Its Impact on Students' Arabic Learning Outcomes: Analysis of Learning Strategies at Madrasah Tsanawiyah Negeri 2 Purworejo - Akhmad Shaiful Bakri; Fitri Fatimah; Rosyidah Nur Lailiyah; Mohamad Madum (Pasca Sarjana IAIN Sultan Amai Gorontalo, 2026)
Differentiated learning is an approach that tailors learning to students' readiness, interests, and learning profiles. This study aims to analyze its implementation in improving Arabic learning outcomes at Madrasah Tsanawiyah Negeri 2 Purworejo. Using qualitative methods, data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model (data reduction, presentation, and conclusion). Data validity was maintained through triangulation of sources and methods, as well as member checks and discussions with peers. The results showed that the implementation of differentiated learning at Madrasah Tsanawiyah Negeri 2 Purworejo was successful and had a positive impact on student learning outcomes. The process included diagnostic assessment, teaching plan preparation, and implementation covering four elements: content, process, product, and learning environment. The material is tailored to students' understanding, teaching methods follow learning styles, and students are free to demonstrate their understanding through various forms of assignments. The application of these strategies has increased student activity, motivation to learn, and learning outcomes in Arabic. The novelty of this research lies in the mapping of the implementation of the stages of preparation, implementation, and assessment of differentiated learning in the four maharah (istimā’, kalām, qirā’ah, kitābah). Thus, differentiated learning can be an alternative effective learning strategy to improve Arabic learning outcomes in madrasah.